Periodontal phenotype modification therapy in a patient undergoing orthodontic treatment: a case report - Tenório, Isabelle Silvério; Santos, Maria Vitória Calado Ramalho dos; Bernardino, Ítalo de Macedo; Andrade, Jamesson de Macedo; Sena, Luana Samara Balduino de; Fonseca, Fátima Roneiva Alves; Rodrigues, Rachel de Queiroz Ferreira; Sousa, João Nilton Lopes de (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Introduction: Gingival recessions are mucogingival defects of multifactorial etiology that interfere with aesthetics and function; in many cases these defects require multidisciplinary treatment. Objective: To report a clinical case of gingival recession treatment using a periodontal and orthodontic approach. Case report: Patient a 20-year-old woman, sought the Extension Project of Clinical and Surgical Periodontics (PROEPECC/UFCG) complaining of developing gingival recession in tooth 31, which was poorly positioned in the arch after orthodontic movement. Periodontal examination revealed type 1 gingival recession associated with a prominent labial frenulum, with a gingival height of 3 mm, width of 2 mm, probing depth of 1 mm, and absence of attached gingiva. The root was covered using a subepithelial connective tissue graft removed from the palatal mucosa and coronally positioned flap; in addition, inferior labial frenectomy was performed. After 1 year and 6 months, tooth 31 was again moved to reposition it in the arch. One year and 10 months post-surgery, new periodontal examination was performed to evaluate the mucogingival characteristics of the treated area. The recession was completely covered and there was a 4-mm increase in the attached gingiva. Conclusion: Orthodontics may positively or negatively influence periodontal structures and periodontics may favor the prognosis of tooth movement in a risk area by modifying the periodontal phenotype, increasing its resistance to gingival recession.